PROSPECTIVE ELECTROMECHANICAL SHOCK ABSORBERS (Transport systems and technologies, 2021)
The article considers the issue of the system of the running gear of a high-speed electric train with a body inclination and the system of oscillation recovery. The authors considered the main suspension systems of the electric train body, which are currently used. The main problems of these suspension systems were put forward. Attention is paid to the use of air-spring suspension. The pipe suspension of the VL80 electric locomotive and the construction of the trolley itself are considered. The basic criteria of an estimation of efficiency of perspective electromechanical shock-absorbers on which the comparative characteristic is carried out are defined. The article describes a promising electromechanical shock absorber based on a synchronous linear motor, which can provide both body tilt and damping and recovery of oscillations. The functional scheme of control of two synchronous linear motors which are established on one cart is considered. The operation of the control system of synchronous linear motors is described. The design of a linear DC motor with permanent magnets is described. The functional control scheme of two linear DC motors with permanent magnets is considered. The design of the electromechanical shock-absorber of the Bose company is resulted. The comparative characteristic of three perspective electromechanical shock-absorbers on six criteria is carried out. Conclusions are made and an electromechanical shock absorber is selected, which provides the basic needs of rolling stock.
Keywords: electromechanical shock absorber, recuperation, body tilt, electric rolling stock, oscillations.